If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -8x = x + -4 Reorder the terms: 7 + -8x = -4 + x Solving 7 + -8x = -4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + -8x + -1x = -4 + x + -1x Combine like terms: -8x + -1x = -9x 7 + -9x = -4 + x + -1x Combine like terms: x + -1x = 0 7 + -9x = -4 + 0 7 + -9x = -4 Add '-7' to each side of the equation. 7 + -7 + -9x = -4 + -7 Combine like terms: 7 + -7 = 0 0 + -9x = -4 + -7 -9x = -4 + -7 Combine like terms: -4 + -7 = -11 -9x = -11 Divide each side by '-9'. x = 1.222222222 Simplifying x = 1.222222222
| 35ab-15ab^2= | | 2y+5y=-28 | | 12l=64 | | 3w-8=272 | | 18x^2+27x-18=0 | | d=2p+3 | | -3-7=(a+9) | | 0=-6x^2+12000x-21000000 | | 6-n=26 | | 655557775-876787= | | 0.6x+0.7y=4.2 | | 1-6x=8-7 | | -x+5=12 | | y=4x-2xy-2 | | 24x^3+16x^2+4x-6=0 | | 3x*30=0 | | -x=-36 | | lx+2l-3=15 | | 0=-6x^2+12000x | | -11y+18=-20-9y+4 | | 0.18-0.02(x+1)=-0.02(2-x) | | 3(2+2x)=26 | | 14x-6=10x+4 | | -6x+3+7x=4 | | -2lx+5l=8 | | 2x+4x(38-x)=136 | | bx+a=c | | 12x-6-8x=2x+2-6 | | -14+7m-19m=5m+20 | | 8=v+7 | | 3+6x+7x=-153 | | -2y-15=8y+15 |